AB1253 DETERMINATION OF RISK FACTORS OF DEVELOPMENT OF HYPERURICEMIA IN PROFESSIONAL ATHLETES IN SOME SPORTS. (June 2019) - Chikina, Maria; Eliseev, Maxim; Sheliabina, Olga; Glukhova, Svetlana; Kruglova, Irina; Nasonov, Evgeny; Lila, Alexander
Abstract : Background: Prevalence of hyperuricemia worldwide has been steadily increasing over the past decades and becomes higher with age. The number of studies on the prevalence of hyperuricemia and its role in development of diseases in some social groups is low, yet there is data on its high frequency in professional athletes. Objectives: to assess impact of certain factors upon the risk of development of hyperuricemia in professional athletes in some sports. Methods: the study was performed as retrospective. Out of 753 athletes in six sports, 267 athletes who met the study criteria were selected. The inclusion criteria: professional athletes aged 18-40, serum uric acid level <360 μmol/l, according to screening tests. The exclusion criterion was refusal to undergo a thorough medical examination. Out of 753 athletes, 228 (30.3%) showed high uric acid level in their screening test, 258 (34.3%) athletes refused to undergo a medical examination. 267 people were included in the study, 130 men (48.7%) and 137 women (51.3%), with the mean age of 24.4±5.2 years and the average observation period of 3.0±0.3 years. Parameters under investigation: anthropometric measurements, laboratory tests (serum levels of lactate, creatinine, crude protein, triglycerides, thyroid-stimulating hormone (TSH), AST, ALT, myoglobin, testosterone, uric acid (UA)), glomerular filtration rate (GFR) (using the MDRD formula) with subsequent statistical analysis. Hyperuricemia was defined as SUA level >360 μmol/L. Hypercholesterinemia - as serum cholesterol level >5.0 μmol/L, hypertriglyceridemia - as serum TG level >1.7 mmol/L. High serum creatinine level as >100 μmol/L. Statistical analysis was conducted using the applied programs package of descriptive statistics STATISTICA 12.0 (StatSoft.Inc., USA). Results: Hyperuricemia developed in 60 athletes (22.5%), including 51 (39.2%) men and 9 (6.6%) women. The frequency of risk factor detection was the following: hypercholesterinemia was detected in 91 (34%) professional athletes, hypertriglyceridemia - in 10 (3.7%), reduction in GFR <100mL/min - in 46 (17.2%), BMI >25 kg/m 2 - in 65 (24.3%), BMI >30 kg/m 2 - in 3 (1.1%), arterial hypertension in 0 (0%) professional athletes. The univariate analysis showed that out of all the factors under investigation, the following factors were significantly associated with the development of hyperuricemia: male sex (OR 9.181, 95% CI (4.285;19.674 p<0.001), hypertriglyceridemia (OR – 4.857, 95% CI (1.056;22.339) p=0.042), BMI >25 kg/m 2 (OR – 2.470, 95% CI (1.243;4.909) p=0.01), increased level of CPK (OR – 2.247, 95% CI (1.230;4.105) p=0.008). Age >25 years was associated with lower risk of development of hyperuricemia. According to the multifactor analysis, development of hyperuricemia is associated with male sex (OR – 13.4, 95% CI (3.6;49.6) p=0.00012) and BMI >25 kg/m 2 (OR – 2.4, 95% CI (1.02;5.69) p=0.04). Conclusion: hyperuricemia developed in professional athletes in 22.5% cases in 3.0 years. This study confirms high risk of development of hyperuricemia in professional athletes (22.5% cases in the 3-year observation period) along with low frequency of many traditional risk factors (obesity, hypercholesterinemia, hypertriglyceridemia, chronic kidney disease), which can be linked to the peculiarities of diet. This fact calls for a detailed investigation of the dietary intake of athletes with the purpose of its optimization. Disclosure of Interests: Maria Chikina: None declared, Maxim Eliseev : None declared, Olga Sheliabina Speakers bureau: Berlin Chemie Menarini, Svetlana Glukhova: None declared, Irina Kruglova: None declared, Evgeny Nasonov Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc., Alexander Lila Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc.